PENGARUH MODEL PEMBELAJARAN KOOPERATIF DAN BERPIKIR KRITIS TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN (FAHMUL QIRA’AH) - Adiba Lutfiyyah; Endry Boeriswati; Nuruddin Nuruddin (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2021)
This research aims to investigate the influence of intructional models and critical thinking ability toward reading understanding ability in Arabic language outcome of students at MDT Shibyanul Muslimin Jakarta. This research is quantitative research using design treatment by level 2x2. The instrumen used to assess students critical thingking’s ability is in quentionnaire form, while the instrument used to assess student’s reading understanding ability in Arabic language is in the multiple choice form. The result of the research show that: (1) reading understanding ability in Arabic language outcome of students using cooperative learning tipe STAD model are higher than those reading understanding ability in Arabic language outcomes of students using cooperative learning tipe NHT models, (2) there is interaction effect between learning model and critical thinking on reading understanding ability in Arabic language outcome of students, (3) reading understanding ability in Arabic language outcome of students who has high critical thinking and using cooperative learning tipe STAD model are higher than students using cooperative learing tipe NHT model, (4) reading understanding ability in Arabic language outcome of students who has critical thinking and using cooperative learning tipe STAD model are lower than students using the cooperative learning tipe NHT models.